The Effects of a six-week strength and plyometric training program on dynamic balance of male student athletes - Hamdolah Hadi; Hasan Farhady; Mehdi Bashiri (Vesnu Publications, 2011)
Introduction: The purpose of this study was to determine the effects of a strength and plyometric training on dynamic balance of male athlete students. Methods: Participants were 30 young men with average age of 23.18±4.95yr, average weight of 72.17±3.09kg and average height of 173.58±3.63cm without any history of lower extremity injuries. The subjects were randomly assigned to two groups of strength-plyometric exercises (n=15) and controls (n=15). One day before starting strength and plyometric exercises, dynamic balance assessment via Star Excursion Balance Test (SEBT) was conducted. Exercise program lasted for 6 weeks and throughout this period control group were asked to continue their daily routine activities. Dynamic balance of subjects was re-assessed by SEBT one day after the completion of exercises. Descriptive statistics was used to determine the mean score of subjects' characteristics and reaching distance in eight directions of SEBT. Paired sample t-test was applied to compare pre- and post-test mean scores. T-test for independent groups was also used to compare two groups according to the data of interest. A P value less than 0.05 was considered as significant. Results: In the exercise group all directions of SEBT showed significant differences between pre- and post-test reaching distance by the completion of strength-plyometric training program. According to SEBT data, there was no significant difference between pre- and post-test reaching distance for control group. Significant differences were also observed between exercise and control groups after the applying strength-plyometric training program for all directions of SEBT. Conclusion: With regard to the study results, incorporation of concurrent exercises (strength-plyometric training) in training programs is recommended to reduce risk of injury and to improve the athletes' dynamic balance.   Keywords: Strength- plyometric training, Dynamic Balance